Assessing Learners’ Intercultural Communicative Competence in a Digitalised Era: The Case of Third Year Pupils in Ketroussi Mohamed Middle School, Mostaganem - HAMADOUCH, Abed (l’Université de Mostaganem, 2024)
In today‘s interconnected world, intercultural communicative competence (ICC) is becoming increasingly vital for effective communication. The current research explores the assessment of Algerian middle school learners‘ intercultural communicative competence in the digitalised era. This research adopts a mixed-method approach incorporating both quantitative and qualitative techniques to obtain data. Qualitative approach includes a questionnaire distributed to 42 middle school learners to assess learners‘ knowledge, attitudes, and skills towards the other culture. Moreover, Qualitative approach involves an interview administered to 11 middle school teachers of English language to investigate if teachers teach foreign culture to learners and assess their ICC development. In addition to this, the researcher evaluated third year middle school textbook adopting Xiao‘s (2010) textbook evaluation checklist to highlight whether the textbook as the main source and resource for middle school teachers is reliable and relevant in helping them assessing their learners‘ ICC. Data reveals that third-year middle school learners possess enough knowledge about the target culture. They are tolerant, empathetic, and open-minded to learn about other culture. Learners show that they are aware about differences between their own culture and the host one. Data obtained from the textbook evaluation reveals that the textbook contains shortcoming and that the authors need to take into consideration learners needs in the 21st century as world or global citizens. Learners need to possess skills of communication to communicate effectively with people who are different from them in terms of language and culture. Data gained from the teachers‘ interview shows believe that they have to teach culture to develop learners‘ intercultural communicative competence to make them ready in today‘s interconnected world. Teachers need to be trained on how to teach culture to young learners and how to assess learners‘ ICC
Keywords: Assessment, Learners, Intercultural communicative competence, digitalised era